Comparative study of metaheuristics methods applied to smart grid network in Morocco - Rachid Habachi; Achraf Touil; Abdellah Boulal; Abdelkabir Charkaoui; Abdelwahed Echchatbi (Institute of Advanced Engineering and Science, 2020)
The economic dispatch problem of power plays a very important role in the exploitation of electro-energy systems to judiciously distribute power generated by all plants. The Unit commitment problem (UCP) is mainly finding the minimum cost schedule to a set of generators by turning each one either on or off over a given time horizon to meet the demand load and satisfy different operational constraints, This research article integrates the crow search algorithm (CSA) as a local optimizer of Eagle strategy (ES) to solve economic dispatch and unit commitment problem in smart grid system of two electricity networks: a testing system 7 units and the Moroccan network.. The results obtained by ES- CSA are compared with various results obtained in the literature. Simulation results show that using ES-CSA can lead to finding stable and adequate power generated that can fulfill the need of both the civil and industrial areas.